Study on Electrochemical Fingerprints of Traditional Chinese Medicine Cortex Moutan from Different Origins - Cheng, Wang-Xing; Guan, Yi; Chen, Jia; Fang, Cheng-Wu (Asian Journal of Chemistry, 2012)
The electrochemical fingerprints of traditional Chinese medicine Cortex Moutan from different origins are studied by Belousov-Zhabotinskii (B-Z) oscillation system of H2SO4- HOOCCH2COOH-Ce2(SO4)3-KBrO3. Effects of various variables for the chemical oscillation system were studied. Finally, 12 mL (3 mol/L) sulfuric acid, 6 mL (0.4 mol/L) malonate, 3 mL (0.005 mol/L) cerium ammonium sulfate and 3 mL (0.2 mol/L) sodium bromate, 300 K temperature and 0.300 g of Cortex Moutan powder were chosen as optimal experimental condition. The results indicated that the electrochemical fingerprints of Cortex Moutan from different origins (Tongling, Phenix Mountain, Bozhou, Qingyang) showed significantly different characteristics, such as the maximum potential, induction time and oscillation lifetime, etc. and the electrochemical fingerprints of Cortex Moutan from the same origins showed the same characteristic parameters, so the electrochemical fingerprints could be used to identify the origins of Cortex Moutan. The method is simple, fast and sensitive and does not need sample preparation. Futhermore the electrochemical fingerprint is objective and has good repeatability.